REVITALISASI BUDAYA BEAS PERELEK SEBAGAI MODAL SOSIAL DAN INSTRUMEN EKONOMI KOMUNITAS: STUDI KASUS DI DESA TANJUNGWANGI, KECAMATAN TANJUNGMEDAR, KABUPATEN SUMEDANG - Karyaningsih, Tri Yulianty; Gumilar, Trisna; Khoeruman, Hilman F (Unpad Press, 2025)
The “beas perelek” is an exemplar of local wisdom, a term used to denote the collective knowledge and practices of a particular community. It is a cultural heritage of the Sundanese people, and is characterised by the values of solidarity and social resilience. The objective of this study is to examine the revitalisation of the “beas perelek” culture in Desa Tanjungwangi, Sumedang as a form of strengthening social capital and community economic innovation. A qualitative approach was employed, with data being collected through observation, interviews, and documentation of residents. The results of the study demonstrate that, since 2008, “beas perelek” has undergone a series of reforms in the following areas: institutional, management, and socio-economic function. This tradition is now understood to function not only as a food security system, but also as a vehicle for women's empowerment and for community-based savings and loan activities. The revitalisation of “beas perelek” in Tanjungwangi serves as a tangible illustration of the integration of traditional values and social innovation in the context of village development.